Diagnosis and management of pulmonary arterial hypertension. Issue 4 (13th December 2022) - Cullivan, Sarah; Higgins, Margaret; Gaine, Sean
Pulmonary arterial hypertension (PAH) is a progressive disease of the pulmonary vasculature that is characterised by elevated pressures within the pulmonary vascular tree. Recent decades have witnessed a dramatic expansion in our understanding of the pathobiology and the epidemiology of PAH, and improvements in treatment options and outcomes. The prevalence of PAH is estimated to be between 48 and 55 cases per million adults. The definition was recently amended and a diagnosis of PAH now requires evidence of a mean pulmonary artery pressure >20 mmHg, a pulmonary vascular resistance >2 Wood units and a pulmonary artery wedge pressure ≤15 mmHg at right heart catheterisation. Detailed clinical assessment and a number of additional diagnostic tests are required to assign a clinical group. Biochemistry, echocardiography, lung imaging and pulmonary function tests provide valuable information to assist in the assignment of a clinical group. Risk assessment tools have been refined, and these greatly facilitate risk stratification and enhance treatment decisions and prognostication. Current therapies target three therapeutic pathways: the nitric oxide, prostacyclin and endothelin pathways. While lung transplantation remains the only curative intervention for PAH, there are a number of promising therapies under investigation which may further reduce morbidity and improve outcomes. This review describes the epidemiology, pathology and pathobiology of PAH and introduces important concepts regarding the diagnosis and risk stratification of PAH. The management of PAH is also discussed, with a special focus on PAH specific therapy and key supportive measures. The preceding decades have witnessed significant improvements in our understanding of PAH and an expansion in treatment options. The haemodynamic definition of PAH has been refined and a number of risk assessment tools have been developed. https://bit.ly/3CKYNpV